The Riddle of the Middle: Questioning the Interpretation of the Mixed or Middle-Class Regime of Aristotle’s Politics - Bates, Clifford Angell (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2024)
This paper challenges the argument of the middle-class regime as the embodiment of the mixed regime and is presented as the best regime in practice, or the best regime in most cities. Instead of an account of the best practical regime, that is, of a specific regime form, Aristotle gives one an account on how regimes can achieve moderation and harmony – that is stability through ensuring the role of the meso, the middle, which is between the wealthy and the poor. Aristotle, in his account of this middle and its superiority to either the wealthy and the poor, we navigate through the meaning of what the middle element truly is. So, instead of an account of a specific regime type, we get an account of what moderates and stabilizes regimes generally. Niniejszy artykuł kwestionuje argument, że reżim klasy średniej jest ucieleśnieniem reżimu mieszanego i jest przedstawiany jako najlepszy reżim w praktyce lub najlepszy reżim w większości miast. Zamiast opisu najlepszego praktycznego reżimu, to znaczy konkretnej formy reżimu, Arystoteles przedstawia opis tego, w jaki sposób reżimy mogą osiągnąć umiarkowanie i harmonię – to znaczy stabilność poprzez zapewnienie roli mezo, środka, który znajduje się pomiędzy bogatymi i biednymi. Arystoteles w swoim opisie tego środka i jego wyższości nad bogatymi i biednymi, poruszamy się po znaczeniu tego, czym naprawdę jest element środkowy. Tak więc zamiast opisu konkretnego typu reżimu otrzymujemy opis tego, co ogólnie rzecz biorąc łagodzi i stabilizuje reżimy.
Zagadka środka: kwestionowanie interpretacji mieszanego lub średniego reżimu w polityce Arystotelesa
Keywords: Aristotle’s Politics; polity; middle class; middle class regime; mixed regime; Polityka Arystotelesa; ustrój polityczny; klasa średnia; reżim klasy średniej; reżim mieszany